Modeling of Language Training of the Students of Natural Sciences - Tleuzhanova, G.K.; Stanciu, N.; Mekezhanova, A.B. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The given article is devoted to identifying the components of modeling of foreign-language training of biology students. Currently, this topic is particularly relevant, since the knowledge of a foreign language by modern specialists is a necessity in the context of globalization and provides for the formation of students’ foreign language professional competence. The modeling of foreign language vocational training includes the purpose, task and content of vocational training of a foreign language; analysis of the procedural component of the pedagogical modeling of foreign language teaching; requirements for the qualifications of teachers of natural sciences in terms of learning a foreign language; recommendations on the observance of the conditions for the effective organization of teaching a foreign language; an expected learning outcome. The modeling of foreign language training is based directly on the practical professional orientation of foreign language training and should reflect all modern requirements imposed on graduates by the society, forms and means of foreign language vocational training, as well as the definition of its expected results. The authors of the article have clarified the main goal of foreign language vocational education, considered the requirements for foreign language orientation of qualifications of future biologists, justified the need and socializing potential of active forms of education.
Жаратылыстану ғылыми бағыты студенттерінің тілдік дайындығын үлгілеу
Моделирование языковой подготовки студентов естественнонаучного направления
Keywords: foreign language training; modeling; natural science direction; trilingual education; educational process; foreign language professional competence